2018
DOI: 10.31234/osf.io/5a7ck
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pupillometry tracks fluctuations in working memory performance

Abstract: In 3 experiments, we examined fluctuations in working memory (WM) performance and associated changes in pretrial and task-evoked pupil diameter. Additionally, we examined whether behavioral lapses were accompanied by self-reports of off-task attentional states. The results demonstrated that task-evoked pupillary responses can be used to measure moment-to-moment fluctuations in the success of WM maintenance during delay intervals. Further, when individuals reported being in an off-task attentional state, their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…The cognitive task we have chosen is a visual STM task [ 58 ]. There are several reasons for this selection: First, previous research suggests successful change detection, a measure of visual STM fidelity, may be influenced by attention in infants [ 15 ] and adults [ 59 , 60 ], even in the absence of overt orienting responses. Second, whereas our attention task was designed to elicit rapid and reflexive orienting responses, our visual STM task was not.…”
Section: Methodsmentioning
confidence: 99%
“…The cognitive task we have chosen is a visual STM task [ 58 ]. There are several reasons for this selection: First, previous research suggests successful change detection, a measure of visual STM fidelity, may be influenced by attention in infants [ 15 ] and adults [ 59 , 60 ], even in the absence of overt orienting responses. Second, whereas our attention task was designed to elicit rapid and reflexive orienting responses, our visual STM task was not.…”
Section: Methodsmentioning
confidence: 99%
“…Based on prior work, we predicted that variability in arousal would negatively correlate with recall performance (Madore et al, 2020;Robison & Brewer, 2020;Robison & Unsworth, 2019;Unsworth & Robison, 2015, 2017b, and that intensity of attention would positively correlate with recall performance (Miller et al, 2019;Miller & Unsworth, 2020, 2021. Both hypotheses were supported by the data.…”
Section: Resultsmentioning
confidence: 62%
“…But recently, it has become evident that pupil diameter can be used as a proxy for LC activity (Aston-Jones & Cohen, 2005;Joshi & Gold, 2020;Joshi, Li, Kalwani, & Gold, 2016;Varazzani, San-Galli, Gilardeau, & Bouret, 2015). Consistent with this notion, several recent studies have measured arousal regulation by measuring variability in pupil diameter and found relations among arousal regulation, long-term memory, attention control, sustained attention, working memory capacity, self-reported instances of mind-wandering and distraction, and self-reported media multitasking (Aminihajibashi et al, 2020;Aminihajibashi, Hagen, Foldal, Laeng, & Espeseth, 2019;Madore et al, 2020;Robison & Brewer, 2020, 2021Robison & Unsworth, 2019). Therefore, it appears that arousal regulation is a task-and domain-general individual difference that can impact a host of cognitive performance measures.…”
Section: Pupillary Correlates Of Individual Differences In Long-term Memorymentioning
confidence: 90%
See 1 more Smart Citation
“…Although much previous work has demonstrated the link between attention and VSTM encoding (e.g., Adam, Mance, Fukuda, & Vogel, 2015;Giesbrecht, Weissman, Woldorff, & Mangun, 2006;Murray, Nobre, & Stokes, 2011;Myers, Stokes, Walther, & Nobre, 2014;Robison & Unsworth, 2019), more recent work has demonstrated that performance of VSTM and visual attention tasks is characterized by synchronous fluctuations over time (Balestrieri, Ronconi, & Melcher, 2019;deBettencourt, Keene, Awh, & Vogel, 2019). These findings are taken to support the idea that attentional resources are shared between perceptual representations of visual information and visual information maintained in VSTM (Adam & deBettencourt, 2019).…”
Section: Vstm and Attentionmentioning
confidence: 89%